Strong interferon-gamma mediated cellular immunity to scrub typhus demonstrated using a novel whole cell antigen ELISpot assay in rhesus macaques and humans - Sumonwiriya, M; Paris, D; Sunyakumthorn, P; Anantatat, T; Jenjaroen, K; Chumseng, S; Im-Erbsin, R; Tanganuchitcharnchai, A; Jintaworn, S; Blacksell, S; Chowdhury, F; Kronsteiner-Dobramysl, B; et al. (Public Library of Science, 2017)
Scrub typhus is a febrile infection caused by the obligate intracellular bacterium Orientia tsutsugamushi, which causes significant morbidity and mortality across the Asia-Pacific region. The control of this vector-borne disease is challenging due to humans being dead-end hosts, vertical maintenance of the pathogen in the vector itself, and a potentially large rodent reservoir of unclear significance, coupled with a lack of accurate diagnostic tests. Development of an effective vaccine is highly desirable. This however requires better characterization of the natural immune response of this neglected but important disease. Here we implement a novel IFN-γ ELISpot assay as a tool for studying O. tsutsugamushi induced cellular immune responses in an experimental scrub typhus rhesus macaque model and human populations. Whole cell antigen for O. tsutsugamushi (OT-WCA) was prepared by heat inactivation of Karp-strain bacteria. Rhesus macaques were infected intradermally with O. tsutsugamushi. Freshly isolated peripheral blood mononuclear cells (PBMC) from infected (n = 10) and uninfected animals (n = 5) were stimulated with OT-WCA, and IFN-γ secreting cells quantitated by ELISpot assay at five time points over 28 days. PBMC were then assayed from people in a scrub typhus-endemic region of Thailand (n = 105) and responses compared to those from a partially exposed population in a non-endemic region (n = 14), and to a naïve UK population in UK (n = 12). Mean results at Day 0 prior to O. tsutsugamushi infection were 12 (95% CI 0-25) and 15 (2-27) spot-forming cells (SFC)/106 PBMC for infected and control macaques respectively. Strong O. tsutsugamushi-specific IFN-γ responses were seen post infection, with ELISpot responses 20-fold higher than baseline at Day 7 (mean 235, 95% CI 200-270 SFC/106 PBMC), 105-fold higher at Day 14 (mean 1261, 95% CI 1,097-1,425 SFC/106 PBMC), 125-fold higher at Day 21 (mean 1,498, 95% CI 1,496-1,500 SFC/106 PBMC) and 118-fold higher at Day 28 (mean 1,416, 95% CI 1,306-1,527 SFC/106 PBMC). No significant change was found in the control group at any time point compared to baseline. Humans from a scrub typhus endemic region of Thailand had mean responses of 189 (95% CI 88-290) SFC/106 PBMC compared to mean responses of 40 (95% CI 9-71) SFC/106 PBMC in people from a non-endemic region and 3 (95% CI 0-7) SFC/106 PBMC in naïve controls. In summary, this highly sensitive assay will enable field immunogenicity studies and further characterization of the host response to O. tsutsugamushi, and provides a link between human and animal models to accelerate vaccine development.